2011
DOI: 10.1080/01690965.2010.508878
|View full text |Cite
|
Sign up to set email alerts
|

Intonational phrasing is constrained by meaning, not balance

Abstract: This paper evaluates two classes of hypotheses about how people prosodically segment utterances: (1) meaning-based proposals, with a focus on Watson & Gibson's (2004) proposal, according to which speakers tend to produce boundaries before and after long constituents; and (2) balancing proposals, according to which speakers tend to produce boundaries at evenly spaced intervals. In order to evaluate these proposals, we elicited naïve speakers' productions of sentences systematically varying in the length of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…An interesting question for future research is how prosodic choice is related to segmentation mechanisms, and what causes these “chunking” decisions in general. One argument in the production literature is that phrase boundary placement is constrained by linguistic complexity (Breen, Watson, & Gibson, 2011; Watson & Gibson, 2004). Although some research has suggested that wrap-up effects occur more often at prosodic phrase boundaries in silent reading (Hirotani, Frazier, & Rayner, 2006), future research should be aimed at directly testing the relationship between implicit prosody and silent reading, as well age differences in segmentation strategies in silent reading and phrase-boundary placement in speech.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting question for future research is how prosodic choice is related to segmentation mechanisms, and what causes these “chunking” decisions in general. One argument in the production literature is that phrase boundary placement is constrained by linguistic complexity (Breen, Watson, & Gibson, 2011; Watson & Gibson, 2004). Although some research has suggested that wrap-up effects occur more often at prosodic phrase boundaries in silent reading (Hirotani, Frazier, & Rayner, 2006), future research should be aimed at directly testing the relationship between implicit prosody and silent reading, as well age differences in segmentation strategies in silent reading and phrase-boundary placement in speech.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies of boundary placement that used similar paradigms (Gee & Grosjean, 1983; Ferreira, 1991; Ferreira, 1993; Watson & Gibson, 2004; Breen, Watson, & Gibson, 2011) have found that syntactic and semantic constraints determine boundary placement even when sentences are read out loud or recalled, rather than generated from beginning to end by participants themselves. Participants place boundaries at major syntactic constituents and disprefer placing boundaries between semantically linked words in these tasks.…”
Section: Can Intonational Phrase Structure Be Primed?mentioning
confidence: 95%
“…Sentence phrasing is determined in part by syntactic structure, such that intonational phrase boundaries correlate with syntactic boundaries (Selkirk ; Schafer et al ; Snedeker and Trueswell ; Cooper and Paccia‐Cooper ; Watson and Gibson ; Breen et al ; Gee and Grosjean ; Ferreira ). For example, the boundary in the spoken version of (3b) (indicated by ‘//’) (from Snedeker and Trueswell ) is typically interpreted by listeners as indicating the presence of a syntactic boundary; a listener would interpret the flower as the instrument used for tapping, rather than as a modifier specifying a particular frog to be tapped.…”
Section: Prosody In Spoken Languagementioning
confidence: 99%
“…She manipulated the length of the subject in sentence fragments like (10). Length influences overt boundary placement in that speakers are more likely to place boundaries after longer constituents than shorter ones (Watson and Gibson ; Watson, Breen, and Gibson ; Breen et al ; Ferreira ; Cooper and Paccia‐Cooper ; Gee and Grosjean ). (Hoso'kawa‐to) Mori'sita‐ga si'nyaku‐o kokoro'kara (Hoso'kawa‐and) Morisita‐Nomnew medicine‐Acctrulysinyoositayuuji'ntati‐ni… trustedfriends‐Dat……”
Section: Implicit Prosodic Phrasingmentioning
confidence: 99%